The last kingdom. Season four [videorecording (DVD)] - Dreymon, Alexander, 1983-; Cox, Emily, 1985-; Birthistle, Eva, 1974-; Blackley, Jamie, 1991-; Bouchet, Adrian; Cornwell, Bernard (Universal Pictures Home Entertainment, 2020)
It is a contemporary story of redemption, vengeance and self-discovery set against the birth of England. Adapted from Bernard Cornwell's best-selling series of books it combines real historical figures and events with fiction. Against a turbulent backdrop lives Uhtred. Born the son of a Saxon nobleman, he is orphaned by the Vikings and then kidnapped and raised as one of their own. Forced to choose between the country of his birth and the people of his upbringing, his loyalties are ever tested.